Corporate Governance And Investment Efficiency: Evidence From Financial Sector In Sri Lanka - Anandasayanan, S. (Wayamba University of Sri Lanka, 2025)
Corporate governance is a system that includes the rules and regulations that stakeholders of companies should obey. Investment efficiency refers to how well a firm uses its resources, including capital and labor, to make profitable investments while effectively managing associated risks. The main purpose of this survey is to measure the effect of corporate governance practices implemented by the financial sector on investment efficiency. Fifty financial institutions listed under the financial sector in the Colombo Stock Exchange are randomly selected for this study and the data for the study covers the period from 2017 to 2022. In order to analyze the investment efficiency of the financial sector, return on Assets was used. In addition, to measure the corporate governance, board composition, size of the audit committee, number of meetings and board size were considered as explanatory variables. To analyze the data, the panel data regression analysis was exercised. As per the results, it is quite obvious that the board composition and board meetings have a major impact on the efficiency of investment in the financial sector. These findings depict that, the financial institutions precisely build the board committee in association with independent directors and they conduct meetings to implement the proper plans, in which both of these lead to increase in the investment efficiency. On the other hand, audit committee and board size do not have statistical significance. These findings imply that neither the audit committee size nor the board size has a meaningful impact on investment efficiency. By ensuring the presence of a liaison between corporate governance practice and investment efficiency, the financial sector should adopt the corporate governance requirements suggested by code of best practices in Sri Lanka. When firms adopt corporate governance practices, this implies that those firms are acting on a best interest of the stakeholders.
Keywords: Audit committee; Board meeting; Board size; Board composition and panel data